Evaluation of radiation therapy on grafted and non-grafted defects: an experimental rat model - Milena Suemi IRIE; Isabella Neme Ribeiro dos REIS; Luiz Gustavo Gonzáles OSUNA; Guilherme José Pimentel Lopes de OLIVEIRA; Rubens SPIN-NETO; Priscilla Barbosa Ferreira SOARES (Journal of Applied Oral Science)
Abstract Objective This study aimed to assess the effects of a single-dose radiation therapy (15 Gy) on grafted and non-grafted defects, bone microarchitecture, and collagen maturity. Methodology Bone defects were surgically created in rat femurs. The right femur defect was filled with blood clot (group “Clot”) and the left femur defect by deproteinized bovine bone mineral graft (group “Xenograft”). The animals were divided into two groups: without radiation therapy (nRTX) and with radiation therapy (RTX). Microtomographic (bone volume fraction, BV/TV; trabecular thickness, Tb.Th; trabecular number, Tb.N; trabecular separation, Tb.Sp), histological, and histomorphometric analyses were performed 14 days after the surgery. Two-way ANOVA with Tukey post hoc test was used to compare the groups (α=5%). Results Microtomographic analysis revealed that radiation therapy led to smaller BV/TV and Tb.N in both Clot and Xenograft groups. Regardless of radiation therapy, defects filled with xenografts showed a larger Tb.N. In contrast, the Clot group demonstrated increased BV/TV and Tb.Th. The histomorphometric results were consistent with those obtained by microtomography. Intermediately and densely packed collagen were predominant among the groups. Histological analysis revealed disorganized bone formation bridging the cortical borders of the lesions in the RTX group. The involvement of primary bone with graft particles was commonly observed in all xenograft groups, and radiation therapy did not affect the percentage of bone-graft contact. Conclusion Single-dose radiation therapy affected bone repair, resulting in a smaller amount of newly formed bone in both grafted and non-grafted defects.